COMMUNICATIVE RESOURCE IN ECONOMY AND BUSINESS MANAGEMENT - TAMARA MIKHAYLOVNA Orlova (Мир новой экономики)
Retraction.Despite a great amount of investments in information technology, not all companies manage to stimulate its development and increase its capitalization. The article suggests that for some reason, the management of these companies underestimate the communicative resource that is able to raise the market value of the company by 30%. The essence of the communicative resource in managing the economy and the business is that it determines the nature of intellectual interaction. Information transaction at all levels and through all channels of communication, transforms knowledge into a factor of development. The value of information lies in its exchange, in its transformation into knowledge and into products of intellectual activity. Andthisvalueiscreatedthroughcommunication.